POTENSI PEMBANGUNAN MUSEUM ARAK DALAM MENYIAPKAN DESA TRI EKA BUANA MENJADI DESA WISATA - Sudharma, Kadek Januarsa Adi (JMM - Jurnal Masyarakat Merdeka, 2021)
The biggest arak producer in Bali is precisely located in Tri Eka Buana Village, Sidemen District, Karangasem Regency, Bali Province. With the arak in the village of Tri Eka Buana which is one of the village head's references to advance the Tri Eka Buana Village by giving an idea in the form of a wine museum development which will later become a tourist attraction. The development of the wine museum aims to preserve cultural customs especially the process of making traditional wine and to examine the potential of the wine museum to become a new tourist destination that will affect the economy of the population in the village of Tri Eka Buana. Besides that, Tri Eka Buana Village also plans to make its village a tourist village. However, to get to the tourist village there are several problems, one of which is the lack of village funds that will be used as the construction of the arak museum. In order to achieve the construction of the wine museum in the village of Tri Eka Buana, we therefore help the village by making proposals for the submission of funds to be submitted to related parties which will later be used for the construction of the arak museum.Keywords: Arak Museum, Tourism Village